The occurrence mechanism and damping method of ultra‐low‐frequency oscillations. Issue 5 (20th January 2021) - Wang, Peng; Li, Baohong; Jiang, Qin; Chen, Gang; Han, Xiaoyan; Dragicevic, Tomislav; Liu, Tianqi
Abstract: The ultra‐low‐frequency oscillation (ULFO) problem has reappeared in China recently. Although the hydraulic generator is supposed to have a strong connection to this problem, the conditions for ULFO appearance and detailed reasons are not clear yet. In order to clarify the occurrence mechanism of ULFO, this paper studies each important part of hydraulic generator system, including the governor, exciter and power system stabiliser (PSS). The weak connection is confirmed to have an important impact on the occurrence of the ULFO. Nevertheless, by studying each device's contribution to ULFO through the complex torque coefficient method, it is shown that the negative damping effect of the hydraulic governor will cause the instability in the ultra‐low‐frequency band, while the exciter and the PSS have little influence on ULFO. Additionally, the proportional–integral parameters of the hydraulic governor system are also studied to clarify their influence on ULFO based on the complex torque coefficient method. Based on the above analysis, two damping methods for ULFO suppression are finally proposed. To verify theory and damping methods, the simulations are implemented in PSCAD and PSASP software.